2001
DOI: 10.1097/00002030-200108004-00003
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and individual level analysis of risk factors for HIV infection in four urban populations in sub-Saharan Africa with different levels of HIV infection

Abstract: The strong association between HIV and HSV-2 and male circumcision, and the distribution of the risk factors, led us to conclude that differences in efficiency of HIV transmission as mediated by biological factors outweigh differences in sexual behaviour in explaining the variation in rate of spread of HIV between the four cities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(129 citation statements)
references
References 21 publications
3
123
3
Order By: Relevance
“…Two articles reported on the same data, and their information was therefore combined in the analysis, and they were treated as one study. 12,13 Information about sample characteristics, setting, study design, variables adjusted for and statistical results were extracted from the study by one reviewer (NK), and a confirmatory data extraction and quality appraisal were carried out by a second reviewer (HS). The quality appraisal was conducted using seven appraisal questions adapted from the graphical appraisal tool for epidemiological studies (GATE).…”
Section: Methodsmentioning
confidence: 99%
“…Two articles reported on the same data, and their information was therefore combined in the analysis, and they were treated as one study. 12,13 Information about sample characteristics, setting, study design, variables adjusted for and statistical results were extracted from the study by one reviewer (NK), and a confirmatory data extraction and quality appraisal were carried out by a second reviewer (HS). The quality appraisal was conducted using seven appraisal questions adapted from the graphical appraisal tool for epidemiological studies (GATE).…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] There are undoubtedly many more studies of this sort in the grey literature. Six papers are from Uganda, two based on the Masaka cohort 14 22 and four on the Rakai intervention trial subjects.…”
Section: Resultsmentioning
confidence: 99%
“…11 The sound epidemiological reasons for this are not apparent from the indicators themselves and many lay people may not be conversant with these subtleties.…”
Section: Current Indicatorsmentioning
confidence: 99%
“…39 Fourteen studies provide fair evidence that circumcision is protective against heterosexually acquired HIV infection in men. [40][41][42][43][44][45][46][47][48][49][50][51][52][53] One study with fair evidence found that male circumcision before puberty (specifically before 12 years of age) is more protective than circumcision occurring at a later age. 50 Three large randomized controlled trials provide good evidence of such protection.…”
Section: Hivmentioning
confidence: 99%